Active ascospore discharge in Fusarium solani f. sp. pisi (Nectria haematococca MP VI) - H. G. Kolmark (Fungal Genetics Reports, 1989)
The plant pathogenic fungi Fusarium solani f. sp. cucurbitae and Fusarium solani f. sp. pisi are among the few Fusaria with a known sexual stage.